Conceptual Exploration of Foreign Direct Investment Inflow Towards Improving Food Production in Nigeria - Mbukanma, Ifeanyi (The Journal of Accounting and Management, 2022)
Objectives: Amid Nigeria's ongoing economic backdrop, this study was conducted to explore the potential of Foreign Direct Investment (FDI) inflows towards improving food production in Nigeria. This objective was engineered as Nigeria continued to face food shortages, thus leading to a rise in the prices of food products across the country. On the other hand, FDI was found to have the capacity to leverage the challenges facing food production through imported skills, investment capital, technological innovations, and improving infrastructures that could boost food production advancement. Methodology: This study was conducted using a literature review-based approach. Information on FDI and food production was obtained from journals and publications of previous scholars, both local and international. Findings: The findings of this study revealed that a level of positive relationship exists between FDI inflow and improved food production, as advanced food productivity and processing largely depend on the positive injection of skills, investment capital, technologies, and improving infrastructures. However, it was also revealed that FDI had not attained its optimal level in Nigeria, as the country has been under the yoke of political crises and insecurity, which also affects the sustainable growth of agricultural food production. As such, Nigeria continues to face limited availability and accessibility of food products, increased prices, and continuous importation of food products. Implications: To improve food productivity in Nigeria, stakeholders and policymakers within these sectors should provide an enabling environment to attract more FDI inflow. This recommendation is based on the findings that FDI is a growth engine for advanced food productivity and processing, which could lead to food security in Nigeria. Originality: This study, unlike previous studies, unveiled the potential of FDI inflow towards improved food production in Nigeria, with a theoretical foundation that underpins the integration of FDI variables towards advanced food productivity.